Penetapan Kadar Kalsium Pada Daun Krokot (Portulaca Oleracea L.) Secara Kompleksometri - Zulfisa Zulfisa; Rini Lestari (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2022)
Research on the determination of calcium levels in purslane (Portulaca oleracea L.) leaves has been carried out using the indirect complexometric titration method. Fresh purslane leaves were extracted using 3N HC1, dissolved calcium was added to an excess of 0.05 M NazEDTA solution and the excess Na EDTA was titrated with 0.05 M MgSO4 solution using an EBT indicator. Obtained calcium levels in fresh purslane leaves of 0.1503% w/w.